Navigating Market Volatility through Processing: A Mixed-Methods Study on Value Capture and Business Model Adaptation in Arabica Coffee Farming - Mubarokah Mubarokah; Brilliani Raras Sakapuspa; Aulia Nurul Hikmah; Putra Astaman; Ummu Liyana binti Abdul Aziz (Green Engineering Society, 2026)
Recent shifts in Arabica coffee processing before sale stem from declining farmer profitability caused by low harvest-season prices. This study maps farmer group operations onto a business model canvas and measures the added value of coffee processing. Conducted from January to June 2023 in Trawas District, Mojokerto Regency, East Java Province, was deliberately chosen for its relevance. A mixed-methods approach was used, integrating qualitative analysis with quantitative description. Data were analyzed using value-added calculations and the Business Model Canvas. The findings reveal a modest value-added ratio of 30.1% for green bean processing in Trawas Subdistrict. By contrast, coffee powder processed using the natural method yields a high value-added ratio of 48.75% (IDR 9,750.00). These findings demonstrate that producing Arabica ground coffee generates more added value than processing green beans, primarily due to longer processing times and premium output prices. Nevertheless, the coffee processing business system remains outdated. Broader participation in extension activities is expected to enhance farmers' knowledge, leading to increased productivity in Arabica coffee enterprises.